ENGLISH TEACHING IN THE LENS OF MIND MAPPING: EXAMINING ITS EFFECTIVENESS IN IMPROVING STUDENTS’ READING SKILLS - Nihta V. F. Liando; Eliska L. Dolongtelide; Mister G. Maru (Journal of English Culture, Language, Literature and Education, 2022)
The aim of this research is to reveal the effectiveness of using mind map technique in teaching English to improve students’ reading skills at one vocational high school in North Sulawesi. Experimental study is applied to the controlled and experimental classes. The students in the controlled class were taught using traditional method and in the experimental class by Mind Map Technique. The result of this study shows the mean scores of the test in the experimental class were 81, while the mean scores of the test in control class were 53.3. The finding shows there is an influence of using mind map technique on student reading ability. The students show responsibility and enjoy the learning process. It could be argued that Mind-Map technique can be used as one of the alternatives in teaching reading. Thus, it can be concluded that Mind Map technique is considered effective in teaching reading to students at this school. It helps them to learn the reading content as well as teaches them how to understand the content of English texts. With mind map technique, it was found that the students easily understand the texts. They could also retell the text and were able to answer the questions. Mind Map technique could improve the students’ achievement in reading comprehension text. Teaching reading by using Mind Map technique is effective rather than traditional method